Preparation of water-base immobilized N doped TiO2 using DSAT technique for photocatalytic degradation of methylene blue dye. (2022) - Natar, N.S.; Ikhwan, S.; Nazeri, N.S.; Hamzah, S.R.; Rosli, M.A.; Ghani, N.I.; Ishak, M.A.M.; Razak, S.; Azami, M.S.; Nawawi, W.I.
Highlights: Immobilized N-TiO2 was prepared via water-base DSAT technique. N-TiO2 bandgap energy reduces to 2.80 eV. Immobilized N-TiO2 shows a porous structure and increase the photocatalytic activity. Ethanol and DCM solvents in N-TiO2 has decreased its photoactivity. Abstract: Photocatalytic degradation of TiO2 photocatalyst under suspension mode has widely been studied among researchers. However, the application is limited due to the complexity in separation and non-recyclability of photocatalyst. Immobilization is one of the promising methods to overcome this problem. Most of the prepared immobilization modes showed lower photocatalytic activity compared with the suspension due to the chemical reaction of solvent with modified TiO2 . Therefore, a free solvent or water-base preparation of immobilized TiO2 is critical in retaining its photocatalytic activity. Immobilization via double-sided adhesive tape (DSAT) was introduced previously by our research team, it works the best of others in replacing polymer binder in immobilization system making it a free solvent preparation process. The aim of this research is to prepare immobilized unmodified TiO2 and N doped TiO2 by using water-base DSAT technique. The presence of N element was detected for all modified N doped TiO2 samples confirmed by FTIR and EDX analysis. The N incorporated in modified TiO2 has reduced the band gap energy from 3.0 to 2.8 eV as observed by UV–Vis/DRS analysis. This explained the photoactivity under MB dye degradation is 2.1 times faster under N doped TiO2 where the photodegradation rate for unmodified and optimum N doped TiO2 (TN1-45) were 0.065 and 0.138 min −1 respectively. Immobilized TiO2 /DSAT and TN1-450/DSAT have shown a significant photocatalytic performance where it was only reduced to 15% from suspension to immobilized mode. It can be considered higher performance as compared to the normal immobilization under solvent. It also better than suspension mode by considering of its reusability that able to sustain the photoactivity of immobilized TN1-450/DSAT for at least for 12 cycles.